Redistribution and Group Participation : Experimental Evidence from Africa and the UK - Fafchamps, Marcel; Hill, Ruth Vargas (World Bank, Washington, DC, 2018)
This paper investigates whether the prospect of redistribution hinders the formation of efficiency-enhancing groups. An experiment is conducted in a Kenyan slum, Ugandan villages, and a UK university town and used to test, in an anonymous setting with no feedback, whether subjects join a group that increases their endowment but exposes them to one of three redistributive actions: stealing, giving, or burning. Exposure to redistributive options among group members operates as a disincentive to join a group. This finding obtains under all three treatments -- including when the pressure to redistribute is intrinsic. However, the nature of the redistribution affects the magnitude of the impact. Giving has the least impact on the decision to join a group, whilst forced redistribution through stealing or burning acts as a much larger deterrent to group membership. These findings are common across all three subject pools, but African subjects are particularly reluctant to join a group in the burning treatment, indicating strong reluctance to expose themselves to destruction by others.